Systems and methods for the controllable synthesis of energetic nanocomposites - Patents.com

By dispersing the composite solution of reducing agent and metal oxide and base in the aqueous solution, and adjusting the ratio of base to metal oxide, controlling the core shell structure of energy nanocomposites, the problem of difficult to maintain energy efficiency and performance in large-scale production is solved, and efficient and controllable energy nanocomposite production is achieved.

JP2025510518APending Publication Date: 2025-04-15OQAB DIETRICH INDUCTION INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024550609
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-25
Filing Date
2023-02-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the energy-efficient performance of nano-energy composites in large-scale production.

Method used

The core shell structure and energy efficiency performance of the energy nanocomposite material are controlled by dispersing the composite solution of reducing agent and metal oxide in aqueous solution, and by adjusting the ratio of base to metal oxide.

Benefits of technology

The energy-efficient performance of energy nanocomposites in large-scale production is achieved, and the structure and energy-efficient performance of the material can be adjusted according to the ratio of the base to metal oxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510518000001_ABST
    Figure 2025510518000001_ABST
Patent Text Reader

Abstract

A system and method for synthesizing metastable intermolecular complexes, particularly energetic nanocomposites, is provided. The method includes dispersing a reductive fuel in a first aqueous solution and combining the reductive fuel solution with a second aqueous solution containing a metal oxide and a base to produce a reductive fuel-metal oxide / base solution. The reductive fuel-metal oxide / base solution is mixed and a solid material is filtered and collected from the mixture. The solid material is heated to obtain a reductive fuel-metal oxide energetic nanocomposite. The ratio of base to metal oxide can be varied to achieve a variety of structures including core-shell or well-mixed nanocomposites. The reductive fuel can be aluminum nanoparticles, the metal oxide can be copper oxide, and the base can be ammonia. The method can be used for mass production of energetic nanocomposites and the structure of the energetic nanocomposite can be varied to tune the energetic performance of the energetic nanocomposite.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE Embodiments disclosed herein relate to metastable intermolecular complexes, and in particular to systems and methods for controllably synthesizing a variety of structures of energetic nanocomposites. [Background technology]

[0002] Introduction Metastable intermolecular composites (MICs), an important type of energetic material, typically have a reducing fuel, such as aluminum (Al), magnesium, silicon, and boron, and an oxidizer, including metal oxides and halogen complexes. The redox reaction between the fuel and the oxidizer generates a significant amount of heat and pressure, which can be exploited for many applications. With the advancement of nanotechnology, nanoscale MICs have attracted great interest. Compared with conventional micron-sized or larger MICs, nanoscale MIC materials have a larger surface area of ​​nanoparticles, which enhances the surface contact between the fuel and the oxidizer, while shortening the diffusion length between the fuel and the oxidizer, which shortens the ignition delay. The microstructure and subsequent energetic performance of metastable intermolecular composites (MICs) are mainly determined by their fabrication process.

[0003] Increasing the surface area of ​​MICs does not necessarily lead to the expected performance improvement due to several drawbacks that arise in MIC nanocomposites. For example, phase separation between aluminum fuel and oxidizer significantly reduces the surface contact and reaction rate, and also leads to reactive sintering of aggregated aluminum nanoparticles, which causes the aluminum nanoparticles to lose their inherent properties. In addition, the alumina shell that spontaneously forms on the surface of aluminum nanoparticles prevents direct contact between the aluminum core and the oxidizer nanoparticles, increasing the energy barrier for inducing the reaction. The presence of an inert shell between the aluminum fuel and the oxidizer also significantly complicates the reaction mechanism of aluminum-based MICs, which has yet to be confirmed. In addition, aluminum nanoparticles are extremely sensitive to external stimuli such as electrostatic discharge and mechanical shock, which limits the mass production, transportation, and safe application of MICs.

[0004] Researchers have developed various structures and synthesis routes to overcome these shortcomings of nanoenergetic composites. Marin et al. applied magnetron sputtering to deposit multilayer Al / CuO nanolaminates, which reduced the reaction temperature and avoided the loosening of MIC powder during synthesis, enhancing safety measures. However, this process only yields small amounts of material and has a limited burn rate. Self-assembly methods have been explored as a possible method for bulk fabrication of MICs, which would improve homogeneity and enhance the reactivity of the final product. Self-assembled MICs showed better homogeneity and enhanced surface contact with fuel and oxidizer, improving the reactivity of the fabricated nanoenergetics.

[0005] Among various types of nanoscale MICs, the core-shell structure maximizes the surface contact between the fuel and the oxidizer. Either the reductive fuel or the oxidizer in various shapes can be adopted as the core material, which is completely covered by other components to form the core-shell structure. The core-shell structure provides a complete reaction system. Various core-shell structured MICs have been developed, such as Al / PTFE, Co3O4 / Al, and NiCo2O4 / Al. However, Al / PTFE has a relatively slow reaction rate due to the decomposition kinetics of fluororesin, and nanowires such as Co3O4 / Al and NiCo2O4 / Al require magnetron sputtering for Al deposition, which precludes bulk production. Deng et al. synthesized the core-shell with dense distribution of micron-Al / CuO MICs using precipitation and replacement methods. The diffusion length between the fuel and oxidizer was significantly shortened, which significantly reduced the ignition delay and reaction onset temperature, and also increased the heat release. One-pot synthesis of spherical Al / CuO core-shell structures using wet chemical methods was also performed. A cuprammonium complex layer was first formed on the surface of Al micron-sized particles, which was then calcined to obtain a CuO shell, producing well-covered Al / CuO core-shell particles.In contrast to other core-shell MICs, spherical Al / CuO nanoparticles have attractive properties such as mobility and compatibility to form energy-carrying colloids in flow systems.

[0006] However, there remains a need for synthetic methods for MICs that allow for bulk production while maintaining the energetic performance of the complexes. Summary of the Invention

[0007] summary Provided herein is a method for the controllable synthesis of an energetic nanocomposite, comprising dispersing a reductive fuel in a first aqueous solution to produce a reductive fuel solution, combining a metal oxide and a base in a second aqueous solution in a specific ratio of metal oxide to base to produce a metal oxide-base complex solution, mixing the reductive fuel solution and the metal oxide-base complex solution together to produce a reductive fuel-metal oxide / base solution, filtering solid material precipitated from the reductive fuel-metal oxide / base solution, and heating the solid material to obtain a reductive fuel-metal oxide energetic nanocomposite, wherein the structural and energetic performance properties of the reductive fuel-metal oxide energetic nanocomposite depend on the ratio of metal oxide to base in the metal oxide-base complex solution.

[0008] According to some embodiments, the particular ratio may be a first ratio, where the base is in excess of the metal oxide, and the reductive fuel-metal oxide energy nanocomposite may have a core-shell structure, where the reductive fuel may be the core and the metal oxide may be the shell.

[0009] According to some embodiments, the specific ratio may be a second ratio, where the base is not in excess of the metal oxide, and the reductive fuel-metal oxide energy nanocomposite may have a well-mixed structure.

[0010] According to some embodiments, the reducing fuel may be aluminum nanoparticles, the metal oxide may be copper oxide, the base may be ammonia, the first aqueous solution may be ethanol, and / or the metal oxide may be provided as an oxide precursor.

[0011] According to some embodiments, the metal oxide and / or reducing fuel may be provided from the regolith.

[0012] Provided herein is a system for the controllable synthesis of energy nanocomposites, comprising a disperser for dispersing a reductive fuel in a first aqueous solution to produce a reductive fuel solution, a mixer for mixing the reductive fuel solution with a metal oxide-base complex solution to produce a reductive fuel-metal oxide / base solution, the mixer being capable of varying a specific ratio of metal oxide to base, a filter for recovering solid material from the reductive fuel-metal oxide / base solution, and a heat source for heating the solid material to obtain a reductive fuel-metal oxide energy nanocomposite, the structure of which depends on the ratio of metal oxide to base in the metal oxide-base complex solution.

[0013] According to some embodiments, the particular ratio may be a first ratio, the base may be in excess of the metal oxide, and the reductive fuel-metal oxide energy nanocomposite may have a core-shell structure in which the reductive fuel may be the core and the metal oxide may be the shell.

[0014] According to some embodiments, the specific ratio may be a second ratio, where the base is not in excess of the metal oxide, and the reducible fuel-metal oxide energy nanocomposite may have a well-mixed structure.

[0015] According to some embodiments, the reducing fuel may be aluminum nanoparticles, the metal oxide may be copper oxide, the base may be ammonia, the first aqueous solution may be ethanol, and / or the metal oxide may be provided as an oxide precursor.

[0016] According to some embodiments, the metal oxide and / or reducing fuel may be provided from the regolith.

[0017] Other aspects and features will become apparent to those of ordinary skill in the art upon review of the following description of several exemplary embodiments. [Brief description of the drawings]

[0018] The drawings included herein are intended to illustrate various examples of the articles, methods, and apparatus herein. [Figure 1A] FIG. 1A is a schematic diagram of a method for controllably synthesizing a nanoparticle metastable intermolecular complex using a reducing fuel, a metal oxide, and a base according to a first embodiment. [Figure 1B] FIG. 1B is a schematic diagram of a method for controllably synthesizing nanoparticle metastable intermolecular complexes using a reducing fuel, a metal oxide, and a base according to a second embodiment. [Diagram 2] FIG. 2 is a flow diagram of a basic method for synthesizing nanoparticle metastable intermolecular complexes using a wet chemistry system according to one embodiment. [Diagram 3] FIG. 3 is a flow diagram of a method for controllable synthesis of nanoparticle metastable intermolecular complexes according to the embodiment of FIGS. 1A and 1B. [Figure 4A] FIG. 4A is a schematic diagram of a method for the controllable synthesis of nanoparticle metastable intermolecular complexes with aluminum, copper, and ammonium according to a first set of parameters. [Figure 4B] FIG. 4B is a schematic diagram of a method for the controllable synthesis of nanoparticle metastable intermolecular complexes with aluminum, copper, and ammonium according to a second set of parameters. [Diagram 5] FIG. 5 is a flow diagram of a method for controllable synthesis of nanoparticle metastable intermolecular complexes using aluminum, copper, and ammonium, according to one embodiment. [Figure 6] FIG. 6 is a flow diagram of a method for controllable synthesis of nanoparticle metastable intermolecular complexes using aluminum, copper, and ammonium according to the embodiment of FIGS. 4A and 4B. [Figure 7] FIG. 7 is a series of scanning electron microscopy (SEM) images of Al / CuO core-shell MICs synthesized from various NH3 / Cu ratios. [Figure 8]Figure 8 is a series of EDS mappings of Al / CuO core-shell nanoparticles at various ER and NH3 / Cu ratios. Figures 8A-E show Al / CuO core-shell nanoparticles at ER=2.5 and NH3 / Cu=4. Figures 8F-J are Al / CuO core-shell nanoparticles at ER=2.5 and NH3 / Cu=16. [Figure 9A-C] FIG. 9 is a series of X-ray diffraction (XRD) spectra of various copper compounds. [Figure 10A] FIG. 10A is a graph of Differential Scanning Calorimetry (DSC) results of Al / CuO core-shell nanoparticle / well mixed nanocomposites made with various equivalence ratios (ER) (1.5, 2.0, 2.5, 3.0, and 4.0), according to one embodiment. [Figure 10B] FIG. 10B is a graph of differential scanning calorimetry (DSC) results of Al / CuO core-shell nanoparticles / well-mixed nanocomposites made with various NH3 / Cu ratios (4, 6, 8, and 16), according to one embodiment. [Figure 11A] FIG. 11A is a graph of energy release by Al / CuO core-shell nanoparticles at different equivalence ratios and NH3 / Cu ratios, according to one embodiment. [Figure 11B] FIG. 11B is a graph of onset temperature with Al / CuO core-shell nanoparticles at different equivalence ratios and NH3 / Cu ratios, according to one embodiment. [Figure 11C] FIG. 11C is a graph of the peak temperature of the main exothermic peak from Al / CuO core-shell nanoparticles at different equivalence ratios and NH3 / Cu ratios, according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Detailed Description Various devices or processes are described below to provide examples of each claimed embodiment. The embodiments described below are not intended to limit the claimed embodiments, which may cover processes or devices different from those described below. The claimed embodiments are not limited to devices or processes having all of the features of any one device or process described below, or to features common to multiple or all of the devices described below.

[0020] Provided herein is a controllable method for synthesizing core-shell nanoparticles, where the synthesis product can be switched between core-shell nanoparticles and well-mixed nanocomposites by changing the ratio of the initial components. Core-shell nanoparticles and well-mixed nanocomposites have different energy performance characteristics. Thus, the controllable synthesis method allows customization of the energy performance of the synthesized nanoparticles to create the desired microstructure of the nanocomposite / nanoparticle. That is, by changing the ratio of the initial components, parameters such as energy release, reaction onset temperature, peak temperature, etc. of the resulting synthesized nanoparticles can be adjusted.

[0021] Here, "nanoparticles" can refer to metastable intermolecular complexes, such as AlCuO core-shell nanoparticles, and individual nanoparticles, e.g., aluminum nanoparticles and copper oxide nanoparticles. Here, "nanocomposite" refers to intimately mixed structures of metastable intermolecular complexes, e.g., AlCuO composites that do not have a core-shell structure, but where CuO is complexed at the surface of the Al. Here, "energy nanocomposite" or "nanoparticle / nanocomposite" is meant to represent both core-shell nanoparticles and intimately mixed nanocomposites.

[0022] Also described herein are specific methods and systems for the controllable synthesis of energetic core-shell or well-mixed Al-CuO particles. The methods described herein can be extended to other metals and metal oxides, such that Al particles having metal or non-metal oxide core-shell or other surface structures other than copper can be produced, or metal particles other than aluminum particles of any material known in the art can be produced.

[0023] Advantageously, this method involves a wet chemical process that does not require special equipment, making it a promising candidate for the bulk production of MIC nanoparticles.

[0024] The method involves mixing a reducible fuel with an oxidant, such as a metal oxide in the oxide plus base form. By varying the ratio of oxide to base, the physical and energetic performance properties of the resulting reducible fuel + metal oxide MIC nanoparticle / nanocomposite can be tuned.

[0025] Patent application WO2023019357A1 to Oqab et al. (herein incorporated by reference) shows that changing the ratio of reducible fuel (metal powder) to oxide precursor (metal oxide) changes the energetic performance of the end product of the synthesis, but does not show that changing the ratio of base to metal oxide changes the structure of the end product of the synthesis.

[0026] Referring to FIG. 1A, there is shown a schematic diagram of components of a method 100a for the controllable synthesis of nanoparticle metastable intermolecular complexes using a reducing fuel, a metal oxide, and a base, where the base is in excess of the metal oxide according to a first embodiment.

[0027] The method 100a includes mixing a metal oxide-base complex 120a including a metal oxide (e.g., copper, nickel, iron, etc.) and a base (e.g., ammonia, organic amine) with a reducible fuel 110 (striped circle, only one labeled to reduce confusion) (e.g., aluminum, magnesium, silicon, boron, etc.). The metal oxide and base interact to form a metal oxide-base molecule; for example, if the metal oxide is copper and the base is ammonia, the metal oxide-base molecule will be Cu(OH) x (NO3) y The reducing fuel 110 is dispersed in an aqueous solution, and the metal oxide-base is mixed into the reducing fuel aqueous solution (arrow 130). In the aqueous solution, the metal oxide-base complex exists as ions 122 (solid circles, only one shown to reduce confusion) and 124 (hatched circles, only one shown to reduce confusion) that interact with the reducing fuel 110. For example, in the copper / ammonia example, the ion is Cu(NH3)4 2+ and NO3 - In some embodiments, the metal oxide base may itself be in an aqueous solution prior to mixing. In other embodiments, the metal oxide base may be a solid, or may be in powder form.

[0028] In some examples, the reducing fuel may be a metal powder. The metal powder may be aluminum metal powder. In some examples, the metal powder may include spherical particles. In some examples, the metal powder may include an average particle diameter of 1 micron, 40 nanometers, up to 100 microns, or up to 100 nanometers. In other examples, metal powders of various sizes may be used. In other embodiments, the metal powder may be particulate.

[0029] In other examples, metal powders of other metals may be used, including iron, nickel, titanium, zirconium, magnesium, zinc, lithium, silicon, boron, tin, tungsten, molybdenum, or transition metals, or other metals known in the art.

[0030] In some examples, the reducible fuel (such as metal powder) can be sourced from Earth. In other examples, sources may include recycled space debris, orbiting satellites, or other materials transported from Earth to space. In other examples, the metal powder can be sourced from space. Sources may also include in situ resource utilization, such as materials from the Moon (lunar regolith), Mars (Martian regolith), and / or asteroid sources.

[0031] In some examples, the reducible fuel (such as metal powder) can be sourced from waste products of industrial processes, or products of other combustion processes, or waste disposal from human or robotic activity.

[0032] The aqueous solution in which the reducible fuel is dispersed may be selected from the group consisting of methanol, ethanol, propanol, butanol, pentanol, or combinations thereof, water, or other liquids or fluids known in the art.

[0033] The metal oxide (or oxide precursor) may be selected from CuO, NiO, TiO2, WO3, MoO3, Fe2O3, KMnO4, or other oxides known in the art.

[0034] In some examples, the metal oxides (or oxide precursors) can be sourced from Earth. Such sources include recycled space debris, orbital recycling satellites, or other materials transported from Earth to space. In other examples, the metal oxides (or oxide precursors) can be sourced from space. Such sources include lunar (lunar regolith), Martian (Martian regolith), and asteroid sources.

[0035] In some examples, the metal oxide (or oxide precursor) can be sourced from the waste output of industrial processes, or the products of other combustion processes, or waste disposal from human or robotic activities.

[0036] After the reducing fuel and the metal oxide base are mixed, a reducing fuel / metal oxide base self-assembled mixture 132 a is formed, and the metal oxide base ions reassemble into metal oxide base molecules on the surface of the reducing fuel 110 .

[0037] The mixed solution is filtered to recover the solid material (including the reductive fuel / metal oxide base 132a) and the solid material is heated (arrow 140). As a result of the heating, the base is removed and a reductive fuel / oxide nanostructure 142a is obtained in which only the metal oxide 144 (black dotted circle, only one labeled to reduce confusion) is present on the reductive fuel 110. The nanostructure is a core-shell nanostructure, where the reductive fuel is the core and the metal oxide is the shell.

[0038] In other examples, methods other than filtration can be used to separate the product solids from the solution, which may include centrifugation, evaporation, or other methods known in the art for separating solids from liquids.

[0039] In various embodiments, heating may include calcination, annealing, dessication, induction heating, radiative heating (e.g., electromagnetic frequencies such as microwaves and / or lasers), inductively coupled methods, and / or magnetically coupled methods. In other embodiments, heating may be provided as a secondary source of thermal radiation, such as using solar concentrators and / or exothermic reactions.

[0040] As mentioned above, in the embodiment of Figure 1A, the base is in excess of the metal oxide. This excess ratio of base to metal oxide is essential for the final nanostructure of the reducible fuel / metal oxide to be a core-shell nanostructure, with the surface of the reducible fuel being coated by the metal oxide. In Figure 1A, it can be seen that the coating is well dispersed.

[0041] In FIG. 1B, the method is the same as in FIG. 1A, except that the base is not in excess of the metal oxide.

[0042] 1B, there is shown, similar to FIG. 1A, a schematic diagram of the components of a second embodiment of a method 100b for the controllable synthesis of nanoparticle metastable intermolecular complexes using a reducing fuel, a metal oxide, and a base, where the base is not in excess relative to the metal oxide. The steps of method 100b are identical to those of method 100a, with the only difference being that the ratio of base / metal oxide is different.

[0043] The method 100b includes mixing a metal oxide-base complex 120b including a metal oxide (e.g., copper, nickel, iron, etc.) and a base (e.g., ammonia, organic amine) with a reducible fuel 110 (striped circle, only one labeled to reduce confusion) (e.g., aluminum, magnesium, silicon, boron, etc.). The metal oxide and base interact to form a metal oxide-base molecule; for example, if the metal oxide is copper and the base is ammonia, the metal oxide-base molecule will be Cu(OH) x (NO3) y The reducing fuel 110 is dispersed in an aqueous solution, and the metal oxide-base is mixed into the reducing fuel aqueous solution (arrow 130). In the aqueous solution, the metal oxide-base complex exists as ions 122 (solid circles, only one shown to reduce confusion) and ions 124 (hatched circles, only one shown to reduce confusion) that interact with the reducing fuel 110. For example, in the copper / ammonia example, the ion is Cu(NH3)4 2+ and NO3 - In some embodiments, the metal oxide base may itself be in aqueous solution prior to mixing. In other embodiments, the metal oxide base may be in solid or powder form.

[0044] After the reducing fuel and the metal oxide base are mixed, a reducing fuel / metal oxide base self-assembled mixture 132b is formed and the metal oxide base ions reassemble into metal oxide base molecules on the surface of the reducing fuel 110.

[0045] The mixed solution is filtered to recover the solid material (including the reductive fuel / metal oxide base 132b) and the solid material is heated (arrow 140). Heating results in the removal of the base and results in the reductive fuel / oxide nanostructure 142b where only metal oxide 144 (black dotted circle, only one labeled to reduce confusion) is present on the reductive fuel 110. The nanostructure 142b is a well-mixed nanocomposite where the reductive fuel is not fully covered by the metal oxide and multiple metal oxide molecules of the complex may be present together on the surface of the reductive fuel.

[0046] In various embodiments, heating may include calcining, annealing, desination, or induction heating, radiative heating (e.g., electromagnetic frequencies such as microwave and / or laser), inductive coupling, and / or magnetic coupling methods. In other embodiments, heating may be provided as a secondary source of thermal radiation, such as using solar concentrators and / or exothermic reactions.

[0047] The method 100 does not require specialized equipment and therefore can be used for mass production of energetic nanoparticles / nanocomposites.

[0048] As mentioned above, in the embodiment of FIG. 1B, the base is not in excess of the metal oxide. The ratio of base to metal oxide is essential for the final nanostructure of the reducing fuel / metal oxide to be a well-mixed nanocomposite, where the surface of the reducing fuel is not covered by the metal oxide, but rather single or complex molecules of the metal oxide are distributed unevenly on the surface of the reducing fuel. In FIG. 1B, it can be seen that the reducing fuel is not fully covered and the metal oxide molecules are complexed.

[0049] Different nanostructures of the synthesized MICs have different energy performance properties, which are described below. Therefore, the controllable method described above and further below allows tuning the properties of the final product of the synthesis by varying the NH3 / Cu ratio and the Al / CuO equivalent ratio. This tuning is achieved by changing the structure of the final Al / CuO nanocomposite / nanoparticle product.

[0050] FIG. 2 is a flow diagram of a basic method 200 for the synthesis of nanoparticle metastable intermolecular complexes using a wet chemistry system, according to one embodiment.

[0051] At 202, the reducing fuel is dispersed in the aqueous solution by a disperser, which may be a sonicator or other mechanism or means that allows for the dispersion of the reducing fuel within the aqueous solution.

[0052] At 204, the metal oxide and base are mixed with an aqueous reducing fuel solution.

[0053] At 206, the mixture of reducing fuel, metal oxide and base is filtered to recover solid materials.

[0054] At 208, the solid material is heated to obtain a nanocomposite / nanoparticle MIC product.

[0055] Method 200 represents the standard steps to achieve the final nanocomposite / nanoparticle product of the synthesis. Figure 3, described below, represents a controllable way in which the ratio of metal oxide to base can be altered to tune the structural and energetic performance properties of the final product of the synthesis.

[0056] 3 is a flow diagram of a controllable method 300 for the synthesis of nanoparticle metastable intermolecular complexes according to the embodiment of FIGs. 1A and 1B. The method is the same as method 200, but describes different end products achieved by varying the ratio of metal oxide to base.

[0057] At 302, method 300 is similar to method 200, where a reducing fuel is dispersed in an aqueous solution.

[0058] At 304, method 300 is the same as method 300, where a metal oxide and a base are mixed with the reducing aqueous fuel solution. However, in method 300, step 304 and beyond splits the method into two branches. The first branch occurs when the base is in excess of the metal oxide 304a. The second branch occurs when the base is not in excess of the metal oxide 304b.

[0059] In 306a following 304a and 306b following 304b, the mixture from 304a / b is filtered to recover any solid material.

[0060] In 308a, the solid material made with an excess of base over metal oxide is heated to obtain the core-shell nanoparticle structure MIC.

[0061] In 308b, the solid material made with no excess of base over metal oxide is heated to obtain a well-mixed nanocomposite structure MIC.

[0062] Method 300 does not require specialized equipment and therefore can be used for mass production of energetic particles tuned to have specific energy performance characteristics. Thus, method 300 allows a user to create large quantities of energetic particles targeted to a specific use case, such as a reaction that only occurs at a specific temperature.

[0063] Figures 1-3 illustrate a standard, non-specific method for the wet chemical synthesis of MICs, where the specific structure of the MICs can be tailored to core-shell nanoparticles or well-mixed nanocomposites by changing the ratio of the initial components of the synthesis. Figures 4-11 illustrate a specific embodiment for synthesizing Al / CuO core-shell nanoparticle / well-mixed nanocomposite MICs. Further specific examples of the method shown and described in Figures 4-11 are applied herein to the aluminum (reducible fuel), copper oxide (metal oxide), and ammonia (base) system, but may be generally applied to any configuration of aluminum, metal oxide, and base suitable for the synthesis of nanocomposite / nanoparticle metastable intermolecular complexes.

[0064] FIG. 4A is a schematic diagram of a method 400a for controllable synthesis of nanoparticle metastable intermolecular complexes with aluminum, copper, and ammonium according to a first set of parameters.

[0065] FIG. 4B is a schematic diagram of a method 400b for controllable synthesis of nanoparticle metastable intermolecular complexes with aluminum, copper, and ammonium according to a second set of parameters.

[0066] Method 400a involves mixing aluminum nanoparticles 410 (empty circles, only one labeled to reduce confusion) with a cuprammonium complex 420a. In the embodiment of Figure 4A, ammonia (base) is in excess over copper oxide (metal oxide).

[0067] The aluminum nanoparticles 410 are in the form of an aqueous solution created by dispersing the aluminum nanoparticles in ethanol by sonication in a sonication bath. The cuprammonium complex 420a is created by mixing an ammonia solution with a Cu(NO3)2·2.5H2O solution in ethanol. The ammonia is in excess of the copper oxide in the cuprammonium complex solution.

[0068] The aluminum solution and the cuprammonium solution are mixed (arrow 430). In the solution, the cuprammonium complex forms Cu(NH3)4 which interacts with the aluminum 410. 2+ Ion 422 (black circle, only one shown to avoid confusion) and NO3 - It exists as ion 424 (hatched circle, only one shown to avoid confusion).

[0069] After aluminum and cuprammonium are mixed, an Al / Cu-NH3 self-assembled mixture 432a is formed, in which the reassembled Cu(NH3)4 2+ Ions and NO3 - The ions reassemble into Cu-NH3 on the surface of the aluminum nanoparticles 410.

[0070] The mixed solution is filtered to recover the solid material (containing Al / Cu-NH3 432a), and the solid material is calcined (arrow 440). As a result of the calcination, the ammonia element is removed, and an Al / CuO nanostructure 442a is obtained in which only copper oxide 444 (black dotted circle, only one labeled to reduce confusion) is present on the reducing fuel 410. The nanostructure is an Al / CuO core-shell nanostructure, with aluminum nanoparticles 410 as the core and copper oxide (CuO) as the shell.

[0071] As mentioned above, in the embodiment of FIG. 4A, ammonia is in excess of copper oxide. This excess ratio of ammonia to copper oxide is essential for the final nanostructure of Al / CuO to be a core-shell nanostructure, with the surface of the aluminum nanoparticles being coated with copper oxide. In FIG. 4A, it can be seen that the coating is well performed, with the CuO evenly distributed on the surface of the aluminum nanoparticles.

[0072] In FIG. 4B, the method is the same as in FIG. 4A, but the ammonia is not in excess of the copper oxide.

[0073] Referring now to Figure 4B, there is shown a schematic diagram of components of a method 400b for the controllable synthesis of nanoparticle metastable intermolecular complexes using aluminum, copper oxide, and ammonia according to a second embodiment in which ammonia is not in excess relative to copper oxide, similar to Figure 1A. The steps of method 400b are identical to those of method 400a, with the only difference being the ammonia / copper oxide ratio.

[0074] Method 400a involves mixing aluminum nanoparticles 410 (empty circles, only one labeled to reduce confusion) with a cuprammonium complex 420a. In the embodiment of Figure 4A, ammonia (base) is not in excess of copper oxide (metal oxide).

[0075] The aluminum nanoparticles 410 are in the form of an aqueous solution created by dispersing aluminum nanoparticles in ethanol by sonication in a sonication bath. The cuprammonium complex 420a is created by mixing an ammonia solution with a Cu(NO3)2·2.5H2O solution in ethanol. The ammonia is not in excess of the copper oxide in the cuprammonium complex solution.

[0076] The aluminum solution and the cuprammonium solution are mixed (arrow 430). In the solution, the cuprammonium complex forms Cu(NH3)4 which interacts with the aluminum 410. 2+ Ion 422 (black circle, only one shown to avoid confusion) and NO3 - It exists as ion 424 (hatched circle, only one shown to avoid confusion).

[0077] After aluminum and cuprammonium are mixed, an Al / Cu-NH3 self-assembled mixture 432a is formed, in which the reassembled Cu(NH3)4 2+ ions and NO3 - The ions reassemble into Cu-NH3 on the surface of the aluminum nanoparticles 410.

[0078] The mixed solution is filtered to recover the solid material (containing Al / Cu-NH3 432a), and the solid material is calcined (arrow 440). As a result of the calcination, the elemental ammonia is removed, and an Al / CuO nanostructure 442a is obtained in which only copper oxide 444 (black dotted circle, only one labeled to reduce confusion) is present on the aluminum nanoparticles 410. This nanostructure is a well-mixed nanocomposite of Al / CuO, where the aluminum nanoparticles 410 are not sufficiently covered by CuO, and CuO may have complexed to form groups or chains of CuO molecules on the surface of the aluminum nanoparticles.

[0079] As mentioned above, in the embodiment of Figure 4A, the ammonia is not in excess of the copper oxide. The ratio of ammonia to copper oxide is essential for the final nanostructure of Al / CuO to be a well-mixed nanocomposite (not a core-shell structure) and for the surface of the aluminum nanoparticles to not be covered by the copper oxide. In Figure 4A, it can be seen that the aluminum is not fully covered and the CuO is complexed.

[0080] In other embodiments of the basic method described in Figures 1-4, other reducing fuels, metal oxides, and bases can be used. The specific ratio of base to metal oxide that allows the final product to have a variety of structural compositions may vary depending on the particular reducing fuel, metal oxide, and base employed. That is, in some embodiments, the base may always be in stoichiometric excess over the metal oxide, but the degree of excess may determine whether a core-shell structure or a well-mixed structure is achieved for the final product. Similarly, the reverse is true, and in some embodiments, the metal oxide may always be in stoichiometric excess over the base.

[0081] Different nanostructures of the synthesized MICs have different energy performance characteristics, which are discussed below.

[0082] FIG. 5 is a flow diagram of a basic method for synthesizing nanoparticle metastable intermolecular complexes using aluminum, copper, and ammonium according to one embodiment.

[0083] At 502, the aluminum nanoparticles are dispersed in the aqueous solution by sonication. In other embodiments, any other sufficient mechanism for dispersing the aluminum nanoparticles in the aqueous solution may be employed.

[0084] At 504, copper oxide and ammonia are mixed with the aluminum solution in the form of an aqueous cuprammonium complex solution. The aluminum and cuprammonium may be mixed by stirring, for example, a magnetic stir bar and stir plate may be used. In other embodiments, the aluminum and cuprammonium may be mixed together by any mixing means, for example, a stirrer may be used. In other embodiments, magnetohydrodynamics may be used to mix the materials together using magnets and / or electromagnets.

[0085] At 506, the mixture of aluminum and cuprammonium is filtered to recover any solid material. The mixing of aluminum and cuprammonium produces a precipitate that includes aluminum nanoparticles, cuprammonium, and aluminum cuprammonium (Al / Cu-NH3).

[0086] At 508, the solid material is calcined to obtain aluminum copper oxide (Al / CuO) nanoparticles having a core-shell structure as shown in Figure 4A above. Calcination may include heating the solid to an elevated temperature for a period of time, for example, 230°C for 3 hours.

[0087] FIG. 6 is a flow diagram of a method for controllable synthesis of nanoparticle metastable intermolecular complexes using aluminum, copper, and ammonium according to the embodiment of FIGS. 4A and 4B.

[0088] At 602, method 600 is the same as method 500. At 602, aluminum nanoparticles are dispersed in an aqueous solution by sonication. In other embodiments, any other sufficient mechanism for dispersing aluminum nanoparticles in an aqueous solution may be employed.

[0089] At 604, method 600 is the same as 504 of method 500. At 604a / b, copper oxide and ammonia are mixed with the aluminum solution in the form of an aqueous cuprammonium complex solution. The aluminum and cuprammonium may be mixed by stirring. In other embodiments, the aluminum and cuprammonium may be mixed together by any mixing means. In other embodiments, magnetohydrodynamics may be used to mix the materials together using magnets and / or electromagnets.

[0090] However, in method 600, step 604 (and the method thereafter) is split into two branches. The first branch 604a occurs when the base is in excess of the metal oxide. The second branch 604b occurs when the base is not in excess of the metal oxide.

[0091] In 604a followed by 606a and 604b followed by 606b, the mixtures from 604a and b, respectively, are filtered to recover any solid material. The mixing of aluminum and cuprammonium produces a precipitate including aluminum nanoparticles, cuprammonium, and aluminum cuprammonium (Al / Cu-NH3).

[0092] In 608a, the solid material prepared with ammonia in excess of copper oxide is calcined to obtain core-shell nanoparticle structured Al / CuO MICs.

[0093] In 608b, the solid material produced with no excess of ammonia over copper oxide is calcined to obtain a well-mixed nanocomposite structured Al / CuO MIC.

[0094] Method 600 does not require specialized equipment and therefore can be used for mass production of Al / CuO energetic particles tailored to have specific energy performance characteristics, i.e., method 600 allows a user to create large quantities of Al / CuO energetic particles targeted to a specific use case, such as a reaction that only occurs at a specific temperature.

[0095] Further details of the formation mechanism and controllable synthesis of Al / CuO energetic nanocomposites are discussed below, including the energy performance properties of various structures created in association with specific ratios of ammonia to copper during synthesis and specific equivalent ratios of aluminum to copper in the Al / CuO nanoparticles / nanocomposites.

[0096] The following Figures 7-11 show and illustrate the results of various experiments performed on the products of the method described above in Figures 3-6.

[0097] In one embodiment, 50 mg of Al nanoparticles were dispersed in 15 mL of ethanol in a sonication bath for 2 h, while a calculated amount of ammonia solution was added to a solution of Cu(NO3)2·2.5H2O in 10 mL of ethanol to prepare a cuprammonium complex suspension. After 2 h of sonication, the cuprammonium complex (Cu-NH3 complex) suspension and an additional 25 mL of ethanol were added to the Al dispersion. The mixture was stirred for 1 h and then filtered. The solid (Al / Cu-NH3 mixture) was collected and annealed at 230 °C for 3 h to obtain the final Al / CuO core-shell product.

[0098] With excess ammonia, the Al / Cu-NH3 mixtures quickly settled to the bottom of the vessel, leaving a nearly clear supernatant. No significant concentration gradients due to slow settling processes or low-density aggregates were observed, indicating that a self-assembly process led to the formation of denser solids in all Al nanoparticle and Cu-NH3 complex mixtures.

[0099] Without excess ammonia, the precipitation process of the Al / Cu-NH3 complex mixture was much slower and the supernatant became clear only after a few days. Thus, the amount of ammonia relative to copper significantly altered the self-assembly process, the structure and energetics of the final complex (see below).

[0100] Two variables, equivalence ratio (ER) and ammonia / copper ratio (NH3 / Cu ratio), were investigated to see how they affect the formation and energy performance of the final Al / CuO product. The nominal equivalence ratio of the Al / CuO final product was calculated using the molar amounts of active aluminum core and copper nitrate as shown in the following equation:

[0101]

number

[0102] The ammonia to copper ratio was calculated from the molar amounts of ammonia and copper nitrate used to obtain the Cu-NH3 complex suspension. The concentration of ammonia used in the calculation was 30%. Samples with equivalence ratios of 1.5, 2.0, 2.5, 3.0, and 4.0 and copper to ammonia ratios of 4, 6, 8, and 16 were analyzed. The NH3 / Cu ratio of 4 was Cu(NH3)4 2+ This is the stoichiometric value that forms a complex coordination ion of NH3 / Cu. Therefore, in the sample with NH3 / Cu = 4, copper was in excess. Some examples of the amounts of raw materials are shown in Table 1.

[0103] [Table 1]

[0104] A calculated amount of aqueous ammonia was added to the Cu(NO3)2·2.5H2O / ethanol solution to prepare two Cu-NH3 complex samples with NH3 / Cu ratios of 4 and 16. The precipitate was filtered and dried overnight at 70°C to obtain the target product.

[0105] As a standard sample set for comparison with the core-shell samples, five reference Al / CuO samples of corresponding equivalence ratios were prepared using ultrasonic treatment.

[0106] Figure 7 is a series of scanning electron microscope (SEM) images of Al / CuO core-shell MICs synthesized from various NH3 / Cu ratios. Figure 7A shows Al nanoparticles. Figures 7B and 7C show Al / CuO nanoparticles / nanocomposites at ER=2.5 and NH3 / Cu=4. Figures 7D, 7E, and 7F show Al / CuO nanoparticles / nanocomposites at ER=2.5 and NH3 / Cu=16.

[0107] Figure 8 is a series of EDS mappings of Al / CuO nanocomposites / nanoparticles at various ER and NH3 / Cu ratios. Figures 8A-E show Al / CuO nanocomposites / nanoparticles at ER=2.5 and NH3 / Cu=4. Figures 8F-J show Al / CuO nanocomposites / nanoparticles at ER=2.5 and NH3 / Cu=16.

[0108] The aluminum nanoparticles are mostly around 100 nm in diameter (60-200 nm) as shown in Figure 7A, with some impurities such as larger particles around 1 micron in diameter. The uncoated aluminum nanoparticles were almost perfectly spherical and showed very smooth surfaces. On the other hand, the Al / CuO core-shell nanoparticles show a completely different morphology as shown in Figure 7B-F.

[0109] Figures 7B and C show Al / CuO nanocomposites synthesized when Cu was in slight excess (NH3 / Cu calculated ratio of 4). There are many small nanoparticles in the sample, indicating the formation of CuO in the sample. The CuO nanoparticles formed are smaller than the Al nanoparticles shown in 7A, roughly 20–60 nm. The CuO nanoparticles form some irregular clusters, which is probably due to the aggregation of the nanoparticles themselves. The coating of CuO on the Al nanoparticles is not well developed. As shown in Figure 7C, only a small portion of the Al nanoparticles are well coated, while the majority of the Al nanoparticles remain only partially coated or uncoated. The EDS results in Figures 8A–E confirm the homogeneous distribution of Al and CuO throughout the sample. Thus, rather than Al / CuO “core-shell” nanoparticles, the sample is better described as a well-mixed Al / CuO nanocomposite synthesized by wet chemical methods when copper was in slight excess relative to the ammonia in the complex.

[0110] Figures 7D-F are SEM images of Al / CuO core-shell nanoparticles with excess ammonia (calculated NH3 / Cu ratio is 16). Unlike Figure 7B, there is no evidence of CuO cluster formation as shown in Figure 7D, and Al and CuO nanoparticles are more uniformly distributed in the sample as confirmed by the EDS mapping in Figures 8F-J. Compared with Figure 7C, the formation of "core-shell" Al / CuO is much better in Figure 7E. Most of the Al particles are well coated or partially coated while there are still some uncoated Al remaining. A close-up of some of the well-coated Al / CuO core-shell nanoparticles is shown in Figure 2F. Figures 7E and F show that the CuO nanoparticles are smaller than the Al nanoparticles and therefore can assemble on the Al surface to form a shell. Thus, the excess amount of NH3 promotes the formation of core-shell structured Al / Cu-NH3 complexes, resulting in better Al / CuO core-shell nanostructures after calcination.

[0111] 9A-C are a series of X-ray diffraction (XRD) spectra of various copper compounds.

[0112] It was hypothesized that the different Al / CuO structures of the final energy nanocomposites produced from different NH3 / Cu ratios were due to different Cu-NH3 complex structures precipitated on the Al nanoparticle surface. To compare the crystal structures of the Cu-NH3 complex precipitates formed from different NH3 / Cu ratios of 4 and 16, XRD of two Cu-NH3 complex samples was measured, as shown in Figure 9. The two curves in Figure 9A show peaks at almost the same 2θ values, but with significantly different intensities, indicating the presence of multiple complexes in the Cu-NH3 complex. Two types of copper complexes correspond well to both the XRD data and the experimental procedure: Cu(NH3)4(NO3)2 (shilovite) and Cu(OH)3(NO3) (rouaite). Comparing the characteristic peaks at 2θ=12.8° (ruite), 15.2°, 21.3°, and 31.0° (syllovite), it was found that the sample with excess ammonia (NH3 / Cu ratio = 16) contained more syllovite (Cu(NH3)4NO3), while the sample with poor ammonia (NH3 / Cu ratio = 4) contained more ruite (Cu(OH)3(NO3)). 2+ At low ammonia concentrations, Cu is formed in environments that are neither acidic nor alkaline. 2+ and OH - Competing reactions between the two become more important.

[0113] When the cuprammonium complex suspension was added to the Al / ethanol dispersion, two different types of suspended matter, Al particles and Cu-NH3 complexes, coexisted in the mixture, and both precipitated. However, these two precipitates did not precipitate separately, but assembled into a core-shell structure of Al / Cu-NH3 complexes. This is thought to be driven by the solubility equilibrium of Cu-NH3 complexes in ethanol and the electrostatic forces between Al particles and Cu-NH3 complexes. In a typical solubility equilibrium of ionic compounds, the dissolution process of the solid precipitate and the precipitation process of the dissolved ions occur simultaneously, and a dynamic equilibrium state is reached when the dissolution and precipitation rates are equal, which happened for Cu-NH3 complexes in ethanol. However, when the precipitate of Cu-NH3 complexes and Al particles coexisted in ethanol, the precipitation process was different.

[0114] The Al / alcohol dispersion has a positive surface charge due to the oxidized shell of the Al particles. When the solution becomes alkaline by adding an aqueous ammonia solution, it becomes neutral or negative, especially when the pH exceeds 9. The Al nanoparticles were dispersed in ethanol under ultrasonic treatment and showed a positive surface charge before the addition of the Cu-NH3 complex. The components that coexisted in the mixture at the time of addition are shown in Table 2 below. When the mixture is poor in ammonia, for example, when the NH3 / Cu ratio is 4, the mixture has a positive surface charge of Cu. 2+ The amount of NH3 available was insufficient to completely react with the Cu, and the alkalinity was weak. Therefore, Al exhibited a nearly neutral surface charge, while Cu 2+ is Cu(NH3)4 2+ Instead of Al, they formed more Cu(OH)n. Therefore, there was no significant electrostatic force between Al and the Cu-NH3 complex. The mixture of Al and Cu-NH3 complex was then filtered and calcined, resulting in the formation of a well-mixed Al-CuO nanocomposite. However, when the mixture was rich in ammonia, e.g., NH3 / Cu ratio = 16, the mixture was more alkaline. As a result, the Al nanoparticles showed a more negative surface charge, and the Cu 2+ reacts more with ammonia, mainly Cu(NH3)4 2+ was formed in the precipitate. Thus, the negative Al nanoparticles and the dissolved positive Cu(NH3)42+ The electrostatic forces between the two induce self-assembly between the components to form a core-shell Al / Cu-NH3 complex structure, which is then calcined to obtain the final core-shell Al / CuO nanostructure. In other samples, when NH3 / Cu was 6 or 8, the structure of the final product was intermediate between these two extreme conditions, but still, NH3 was strongly related to Cu. 2+ The Al / Cu-NH3 mixture was able to precipitate within a few hours, and therefore, in these samples, the product was considered to be close to core-shell Al / CuO.

[0115] [Table 2]

[0116] 10A is a graph of differential scanning calorimetry (DSC) results of Al / CuO nanoparticles / nanocomposites made with various equivalence ratios (ER) (1.5, 2.0, 2.5, 3.0, and 4.0) according to one embodiment, and FIG 10B is a graph of differential scanning calorimetry (DSC) results of Al / CuO nanocomposites / nanoparticles made with various NH3 / Cu ratios (4, 6, 8, and 16) according to an embodiment.

[0117] FIG. 11A is a graph of energy release by Al / CuO core-shell nanoparticles at different equivalence ratios and NH3 / Cu ratios, according to one embodiment. FIG. 11B is a graph of onset temperature by Al / CuO core-shell nanoparticles at different equivalence ratios and NH3 / Cu ratios, according to one embodiment. FIG. 11C is a graph of peak temperature of the main exothermic peak by Al / CuO core-shell nanoparticles at different equivalence ratios and NH3 / Cu ratios, according to one embodiment. FIG. 11A shows energy release for NH3 / Cu ratios and ER shown in FIGS. 10A and B. FIG. 11B shows onset temperature of the reaction for NH3 / Cu ratios and ER shown in FIGS. 10A and 10B. FIG. 11C shows peak temperature of the main reaction for NH3 / Cu ratios and ER shown in FIGS. 10A and 10B.

[0118] DSC measurements of all the fabricated Al / CuO samples with different equivalent ratios (ER) and NH3 / Cu ratios were carried out to analyze the energetic reaction pathways and potentials, as shown in Figures 10A and 10B. The energy release values ​​in Figures 10A and 10B show the exact curves of energy release, not the average values ​​of the corresponding samples. The main parameters, including the energy release, onset, and peak temperatures of the main reactions, are interesting because they help determine the energetic reaction pathways and complex structures. The curves are shown in Figures 11A, 11B, and 11C.

[0119] Figure 10A compares the representative curves of samples with different ER when the NH3 / Cu ratio is fixed at 6. Curves 1001, 1002, 1003, 1004 and 1005 represent ER of 1.5, 2.0, 2.5, 3.0 and 4.0, respectively. All the curves showed the main reaction peak between 520 and 660 °C. The main reaction occurred below the melting point of Al (665 °C), indicating that it is a reaction in the condensed phase. The detailed reaction pathway is thought to be triggered by the diffusion of Al cores from the Al2O3 shell through the cracks formed during crystallization from the amorphous phase to the γ phase at 350 °C. The diffused Al cores come into contact with the CuO shell, forming local hot spots, which promote the diffusion of Al cores, thus accelerating the reaction. The samples with ER of 2.5 and 3.0 showed the highest energy release. In the lower ER sample, a second exothermic reaction shoulder was observed between 680 and 800 °C, possibly due to the reaction of excess CuO with the generated co-oxidant. The second reaction was very small compared to the main reaction peak, indicating that most of the material had reacted before the Al melted.

[0120] Figure 10B shows different NH3 / Cu ratios with ER fixed at 3.0. Curves 1006, 1007, 1008, 1009, and 1010 represent NH3 / Cu ratios of 4, 6, 8, 16, and the reference sample Al / CuO, respectively. In the normal ultrasonic mixing sample, the reaction continued until about 690 °C. This indicates that part of the reaction occurs after the melting of Al nanoparticles due to the physical distance between the Al nanoparticles and CuO nanoparticles. The main reaction peaks shown in the DSC curves of Al / CuO core-shell nanoparticles in Figures 10A and 10B are all completed before the melting of Al at 660 °C, indicating that the main reaction is the condensed phase reaction of fuel and oxidizer. Samples prepared with a slight excess of ammonia (NH3 / Cu) showed the highest energy release for the same ER sample at 3.0, as shown in Figure 11, which was also the case for the other ER samples. When ammonia is slightly in excess relative to copper, Al and Cu(NH3)4 2+ showed sufficient surface charge to self-assemble into core-shell structures, and there was not much water to react with the Al nanoparticles to deactivate them. If the NH3 / Cu ratio was too high, the water in the aqueous ammonia solution could partially deactivate the aluminum cores during the synthesis. Thus, when the NH3 / Cu ratio was 6, good core-shell Al / CuO nanoparticles were formed with minimal Al deactivation, leading to the highest energy release. For the Al / CuO core-shell samples with high NH3 / Cu ratios, a discrete second peak can be seen in Figure 6B. This reaction could have arisen from the reaction of unreacted CuO with the Al-Cu co-oxidant after the main reaction, or from the reaction of unreacted CuO trapped within the Al2O3 shell thickened by excess water during the synthesis with the unreacted Al cores.

[0121] Compared with Al / CuO mixed by ultrasonication, the core-shell Al / CuO nanoparticles did not show high energy release, as shown in Figure 11A. However, the characteristic temperatures of the reaction changed significantly. Apart from the complete temperature of the main reaction mentioned earlier, the onset and peak temperatures of the main reaction also decreased. The decrease in onset temperature was relatively minor, only about 3-10 °C, indicating that the trigger mechanism of the exothermic reaction was unchanged. However, the peak temperature of the reaction was significantly decreased due to the close proximity of the fuel and oxidizer in the Al / CuO core-shell structure. When Al diffusion occurred, the reactive fuel could easily contact the oxidizer without traveling a long distance, resulting in a decrease in the peak temperature of 10-25 °C. In the case of excess ammonia, a better core-shell structure was formed, but the results were not conclusive in that the onset and peak temperatures were always lower because the excess moisture from the ammonia deactivated some of the Al and thickened the Al2O3 shell, increasing these values.

[0122] The reaction parameters of the main reaction of the freshly prepared core-shell Al / CuO nanostructures are compared with other Al / CuO structures, as shown in Table 3 below. The Al / CuO core-shell nanoparticles prepared in this study showed the second lowest onset and peak temperatures, only higher than the first peak of another Al / CuO core-shell structure reported by Shi et al. The close proximity of the fuel and oxidizer in the core-shell structure led to the initiation of the reaction at a lower temperature. In addition, most of the reactions showed multiple exothermic peaks, indicating that different reaction pathways occurred during heating. This is attributed to either the heterogeneity of the samples or the large Al particles. However, the core-shell Al / CuO presented here, as was the case in our previous study, showed a single dominant exothermic peak that terminated before the melting of Al, indicating that a homogeneous core-shell structure was formed and a condensed-phase reaction between the fuel and oxidizer was occurring. In terms of energy release, the nanoparticle Al / CuO showed no improvement compared to the samples with multiple exothermic peaks, which is probably due to the partial deactivation of Al by water during the synthesis. However, it should be noted that the energy release of a reaction may be calculated differently by different researchers.

[0123] [Table 3]

[0124] In some examples, the metal oxide or oxide precursor can be sourced from Earth. Such sources include recycled space debris, orbiting satellites, or other materials transported from Earth to space. In other examples, the metal oxide or oxide precursor can be sourced from space. Such sources include lunar (lunar regolith), Martian (Martian regolith), and asteroid sources.

[0125] In some examples, the systems and methods described herein can be modified to produce energetic core-shell particles with different properties, such as different core-shell structures. Such core-shell structures can include core-shell, multi-core-shell, multi-core hollow structures, yolk-shell, multi-core hollow, core mesopore, sandwich core-shell, and embedded structures. In other examples, the core-shell structures or configurations can include core-shell, double shell, multi-shell, concentration gradient, and full concentration gradient.

[0126] The thermite mixtures including microthermites, nanothermites, microenergetic core-shell particles, and nanoenergetic core-shell particles, as described herein and synthesized by the methods and systems herein, can be applied to many applications requiring high density stored energy, high intensity energy, low carbon emission energy or combustion sources, remote operation (including Earth orbit and outer space), and other requirements.

[0127] In some examples, the metal may be combined with an oxidizer, such as air and / or water. The oxidizer is used as a carrier and as a source of oxidation for the metal. In other examples, both the fuel in the form of a thermite and the oxidizer may be present within the same metal particle (e.g., a metal oxide coating on the outside of a metal particle). In some examples, these particles may be referred to as metal fuels (metal, metal, and / or energetic particles, thermites, and / or micro- and / or nano-thermites, etc.).

[0128] Metallic materials may include energetic particles composed of fuel and oxidizer, typically a metal and metal oxide, respectively. Nanothermites contain both oxidizer and fuel within each particle and are 100 nanometers or smaller in size. The energy release per mass of the particle is very large. As an example, metal fuel propellants, including nanothermites, microthermites, or combinations thereof, can be combined with an inert carrier gas, liquid, or fluid to disperse the propellant within a chamber for effective heating and / or combustion, leading to well-controlled heating, structural, power, and thrust generation.

[0129] Metallic materials and / or fuels (e.g., thermite, microthermites, nanothermites) have high energy density and, when mixed with inert gases, liquids and / or carrier fluids, are generally safer to handle and transport than traditional fuels. They can be synthesized, manufactured, transported and stored for future use. Propellants can be manufactured, stored and transported for dispatchable power. Stored energy can be in the form of matter. Fuels can be used for construction, power and propulsion to generate heat.

[0130] In some examples, the energetic core-shell particles can be used as a source for catalytic conversion of carbon dioxide (e.g., atmospheric carbon dioxide), such as thermal, photocatalytic, and electrocatalytic processes for the conversion of carbon dioxide to produce products such as CO, H2, C3OH, C2, or CH, or other desired products resulting from the CO2 conversion process. In some examples, the energetic core-shell particles can be used as a source for catalytic conversion of methane. In other examples, the energetic core-shell particles can be used as a source for catalytic conversion of other greenhouse gases.

[0131] In some examples, nanothermites can be used for propulsion, power generation, energy storage, and energy distribution. In some examples, nanothermites can be used in construction including welding, additive manufacturing, and 3D printing. For example, core-shells can be incorporated into materials for 3D printing to create 3D printable materials with user-defined properties. In some examples, nanothermites may be used as cathodes in batteries. In some examples, nanothermites can be used as filters, such as mesh filters with specific geometries that can specifically target certain particles and prevent these specific particles from passing through the filter.

[0132] In some examples, nanothermites can be used in thermal control systems such as those described in patent application WO2022140864A1 to Oqab and Dietrich, which is incorporated herein by reference.

[0133] In some instances, nanothermites can be applied to ignition systems in which the nanothermites are heated with a laser or induction heating system to initiate ignition of another material. Such ignition devices are more portable than other igniter systems and are suitably disposable.

[0134] In some examples, the spacecraft can synthesize energetic particles that can be applied to an ignition system, where the energetic particles are heated with a laser or induction heating system to initiate ignition of another material. The spacecraft can rendezvous and attach to an uncontrolled object in space, such as space junk, space debris, a satellite at the end of its life cycle, a satellite that has run out of fuel, a second stage, an asteroid, or other space object, to provide motility and / or additional propulsion capabilities.

[0135] In some examples, a spacecraft may transport multiple other spacecraft for operations, logistics, maintenance, point-to-point transportation, or orbit raising.

[0136] In some examples, multiple satellites can be launched and deployed into low orbit to aid in space debris cleanup and space traffic management using laser-assisted ignition systems and energetic particles. Ignition assistance can be done with laser and / or induction heating systems. Sub-satellites with deployable plates including a first layer of weld filler and / or energetic particles, and / or a second layer with energetic particles can be used to act as catalysts that can be ignited using laser and / or induction heating assisted ignition. The deployable plates can be ignited at remote locations using multiple other satellites in different orbits. In other embodiments, ignition can occur from multiple fixed and mobile sources on the ground, in the air (e.g., from drones and / or airships), on water, and / or in space.

[0137] In one embodiment, it may be possible to capture and release space debris, other space objects larger than 10 cm, or asteroids, in order to capture and release uncontrollable space objects, including but not limited to satellites without propulsion systems, and to enable the uncontrollable space objects to be equipped with new propulsion systems and / or refueled or undergo in-orbit maintenance.

[0138] In other embodiments, energetic particles can be used in combination with multiple shaping methods, including but not limited to microemulsion, wet spinning, roll-to-roll casting, spin coating, molding, etc. In some embodiments, shapes such as microspheres, fibers, sheets, coatings, complex shapes, layered shapes, and / or monoliths can be created.

[0139] In other embodiments, energetic core-shells can be used in addition to molecular precursors, nanoparticles, nanofibers, nanotubes, nanosheets, etc. In some examples, microstructures such as particle chains, fibrous structures, and / or laminated flake structures may be added.

[0140] In other embodiments, the satellite system can carry multiple other satellites for in-space applications and services. In some embodiments, the satellite subsystems can be carried on a resupply satellite system that can capture and resupply other satellites in space for servicing, and release those satellites beyond low earth orbit for continued operation or servicing.

[0141] In some examples, the energetic core-shell particles may become embedded into the structure of the system under reaction and / or sintering, hardening processes.

[0142] In some examples, energetic core-shell particles may be reacted in a gas for propulsion application.

[0143] In some examples, the energetic core-shell particles can be applied to space-based applications such as in-space manufacturing for products such as the synthesis of compounds and mixtures that benefit from the microgravity environment and result in improved conditions such as the production of materials relevant to pharmaceuticals and / or other medical applications.

[0144] In some instances, energetic core-shell particles have applications in driving reactions on Earth and in space.

[0145] In some instances, energetic core-shell particles can be applied to refueling satellites in space. In some instances, adding magnetic fuel to a material makes the material more magnetic, allowing the particles to move under varying gravitational forces, and magnetohydrodynamics can be used to move the particles within the system. The magnetic properties of the fuel can be utilized to refuel systems in space.

[0146] Although the above description provides examples of one or more devices, methods, or systems, it will be understood that other devices, methods, or systems are within the scope of the claims as interpreted by one of ordinary skill in the art.

Claims

1. 1. A method for the controllable synthesis of energetic nanocomposites, the method comprising: dispersing a reducing fuel in a first aqueous solution to generate a reducing fuel solution; combining the metal oxide and base in a second aqueous solution in a specific ratio of the metal oxide to the base to produce a metal oxide-base complex solution; mixing said reducing fuel solution and said metal oxide-base complex solution together to produce a reducing fuel-metal oxide / base solution; filtering solid material that precipitates from the reduced fuel-metal oxide / base solution; and heating the solid material to obtain a reducible fuel-metal oxide energy nanocomposite; the structural and energetic performance characteristics of the reductive fuel-metal oxide energy nanocomposite depend on the specific ratio of metal oxide to base in the metal oxide-base complex solution; method.

2. the particular ratio is a first ratio, the base is in excess of the metal oxide; The reducing fuel-metal oxide energy nanocomposite has a core-shell structure in which the reducing fuel is the core and the metal oxide is the shell. The method of claim 1.

3. the particular ratio is a second ratio, the base is not in excess of the metal oxide; The reductive fuel-metal oxide energy nanocomposite has a well-mixed structure; The method of claim 1.

4. The reducing fuel is aluminum nanoparticles.

4. The method according to any one of claims 1 to 3.

5. The metal oxide is copper oxide.

5. The method according to any one of claims 1 to 4.

6. The base is ammonia.

6. The method according to any one of claims 1 to 5.

7. The first aqueous solution is ethanol.

7. The method according to any one of claims 1 to 6.

8. The metal oxide is provided as an oxide precursor.

8. The method according to any one of claims 1 to 7.

9. The metal oxide is provided from regolith.

9. The method according to any one of claims 1 to 8.

10. The reducing fuel is supplied from regolith.

10. The method according to any one of claims 1 to 9.

11. 1. A system for the controllable synthesis of large amounts of energetic nanocomposites, the system comprising: a disperser for dispersing the reducing fuel in the first aqueous solution to generate a reducing fuel solution; a mixer for mixing the reducing fuel solution with a metal oxide-base complex solution to produce a reducing fuel-metal oxide / base solution, the specific ratio of metal oxide to base being variable; a filter for recovering solid materials from the reducing fuel-metal oxide / base solution; a heat source for heating the solid material to obtain a reducible fuel-metal oxide energy nanocomposite; the structure of the reductive fuel-metal oxide energy nanocomposite depends on the ratio of the metal oxide-base in the metal oxide-base complex solution; system.

12. the particular ratio is a first ratio, the base is in excess of the metal oxide; The reducing fuel-metal oxide energy nanocomposite has a core-shell structure in which the reducing fuel is the core and the metal oxide is the shell. The system of claim 11.

13. the particular ratio is a second ratio, the base is not in excess of the metal oxide; The reductive fuel-metal oxide energy nanocomposite has a well-mixed structure; The system of claim 11.

14. The reducing fuel is aluminum nanoparticles. A system according to any one of claims 11 to 13.

15. The metal oxide is copper oxide. A system according to any one of claims 11 to 14.

16. The base is ammonia. A system according to any one of claims 11 to 15.

17. The first aqueous solution is ethanol.

17. A system according to any one of claims 11 to 16.

18. The metal oxide is provided as an oxide precursor.

18. A system according to any one of claims 11 to 17.

19. The metal oxide is provided from regolith.

19. A system according to any one of claims 11 to 18.

20. The reducing fuel is supplied from regolith.

20. A system according to any one of claims 11 to 19.